GE_GERICHTE A/3927/2024 vom 16. Juni 2025 - GE Cour de justice (2025)
INTERDICTION DE CIRCULER;RETRAIT DE PERMIS;CONDUITE SANS AUTORISATION;CAS GRAVE;ANTÉCÉDENT;DURÉE;NÉCESSITÉ;PROFESSION | LCR.16.al1.letf; LCR.16.al2; LCR.16.al3